Prevalence of overweight and obesity among adult Malaysians: an update - Mohamud, W.N.W.; Musa, K.I.; Khir, A.S.M.; Ismail, A.A.; Ismail, I.S.; Kadir, K.A.; Kamaruddin, N.A.; Yaacob, N.A.; Mustafa, N.; Ali, O.; Isa, S.H.M.; Bebakar, W.M.W. (2011)
A total of 4428 adults (>18 years old) from 5 different selected regions in Peninsular and East Malaysia participated in this health survey. Using World Health Organization recommendations for body mass index (HMI), the prevalence of overweight and obesity were found to be 33.6 (95 CI= 32.2, 35.0) and 19.5 (95 CI= 18.3, 20.7) respectively. There were more females who were obese (22.5, 95 CI=20.9, 24.0) compared to males (14.1, 95 CI=12.3, 15.9). Highest prevalence of obesity were among the Indians (24.6, 95 CI=20.3, 29.3), followed closely by the Malays (23.2, 95 CI=21.6, 24.8) and lowest prevalence was among the Chinese subjects (8.2, 95 CI=6.2, 10.6). More than 43 of the 531 younger subjects (<30 years old) were either overweight (20, 95 CI=16.6, 23.6) or obese (13.9, 95 CI=11.1, 17.2). All subjects who claimed to be non-diabetes were required to undergo 75 g glucose tolerance test. Compared to subjects with normal BMI (18.5-24.9 kg/m(2)), there was a 3- and 2-folds increase in the prevalence of newly diagnosed diabetes and impaired glucose tolerance respectively, among obese subjects (BMI >30 kg/m(2)) who initially claimed to have no diabetes. This study highlights a need for more active, inter-sectoral participation advocating a health-promoting environment in order to combat obesity in this country.